2015
DOI: 10.1016/j.vaccine.2015.10.091
|View full text |Cite
|
Sign up to set email alerts
|

Production of high titer attenuated poliovirus strains on the serum-free PER.C6® cell culture platform for the generation of safe and affordable next generation IPV

Abstract: Sabin and rationally-attenuated polioviruses can be grown to high infectious titers and D-antigen yields. Sabin strain infection shows increased productivity on the PER.C6(®) cell platform as compared to the conventional Vero cell platform. Novel cell platforms with the potential for higher yields could contribute to increased affordability of a next generation of IPV vaccines needed for achieving and maintaining poliovirus eradication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 31 publications
2
11
0
1
Order By: Relevance
“…† Sum of three independent analyses. hyper-attenuated strains for vaccine production has been shown 18 and was confirmed for the monitoring of PV neutralizing antibody titers in the QC of immunoglobulin, another essential medicinal, in this work. Using standard virological practices it was possible to produce S19 stocks with infectivity titers that were suitable for QC release testing, the only special requirement for the handling of these strains stemming from their genetically modified nature, i.e., laboratories licensed for work with GMOs might be required.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…† Sum of three independent analyses. hyper-attenuated strains for vaccine production has been shown 18 and was confirmed for the monitoring of PV neutralizing antibody titers in the QC of immunoglobulin, another essential medicinal, in this work. Using standard virological practices it was possible to produce S19 stocks with infectivity titers that were suitable for QC release testing, the only special requirement for the handling of these strains stemming from their genetically modified nature, i.e., laboratories licensed for work with GMOs might be required.…”
Section: Discussionsupporting
confidence: 68%
“…Replication incompetent pseudoviruses or hyper‐attenuated PV strains have been developed and their use in vaccine production, immunogenicity studies, immunotherapy, monitoring of the environment, or neutralizing antibody titers has been proposed. The feasibility to use such hyper‐attenuated strains for vaccine production has been shown and was confirmed for the monitoring of PV neutralizing antibody titers in the QC of immunoglobulin, another essential medicinal, in this work.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Virus production during vaccine manufacture with high yields can significantly decrease costs of goods. We have previously demonstrated that the use of the PER.C6 platform increases volumetric productivity of infection harvests as compared to the Vero-based platform for cIPV strains [ 60 ] and for the Sabin strains [ 61 ]. Use of the highly productive PER.C6 platform for propagation of the CAVA vaccine strains resulted high infectious titer yields (9.4–9.9 Log 10 TCID 50 /ml), comparable to those reached with the Sabin strains (9.2–9.9 Log 10 TCID 50 /ml), which demonstrates potential for significantly reducing cost of goods and consequent vaccine pricing required for global roll-out of an affordable IPV.…”
Section: Discussionmentioning
confidence: 99%
“…Beside these advantages for basic research, some Ad t cell lines such as PER.C6 and AGE.CR.pIX provide a potential platform for the manufacturing of viral vectors and viral vaccines already used in clinical trials (Koudstaal et al, 2009;Lohr et al, 2009Lohr et al, , 2012Pau et al, 2001;Subramanian et al, 2007). These cell lines were shown to be a good substrate for a wide spectrum of viruses, such as poliovirus (Sanders et al, 2015), modified vaccinia Ankara virus (Jordan et al, 2009b) and West Nile virus (Samina et al, 2007). In addition, several Ad t cell lines can be cultivated in suspension allowing a better scalability and flexibility in virus production processes …”
Section: Adenoviral Protein E1a Inhibits the Antiviral Responsementioning
confidence: 99%